2021
DOI: 10.3389/fchem.2021.676631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-(thiophen-2-yl)acetic Acid-Based Lead Compound for mPGES-1 Inhibition

Abstract: We report the implementation of our in silico/synthesis pipeline by targeting the glutathione-dependent enzyme mPGES-1, a valuable macromolecular target in both cancer therapy and inflammation therapy. Specifically, by using a virtual fragment screening approach of aromatic bromides, straightforwardly modifiable by the Suzuki-Miyaura reaction, we identified 3-phenylpropanoic acid and 2-(thiophen-2-yl)acetic acid to be suitable chemical platforms to develop tighter mPGES-1 inhibitors. Among these, compounds 1c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In the last few years, our research group has been involved in the discovery of novel soluble epoxide hydrolase inhibitors (sEHi) and, accordingly, the development of sEH 3D structure-based pharmacophore model represents a valuable strategy for accomplishing this aim [20,21]. Indeed, in addition to the identification of novel compounds with anti-inflammatory and anticancer activity targeting mPGES-1, representing another key target of our research interests [20,[22][23][24], we also focused on other targets belonging to the arachidonic acid cascade to identify multitarget agents with greater benefits than single-target inhibition [25]. In light of these premises, the 3D structure-based pharmacophore model was developed by collecting the necessary spatial definitions from the specific coordinates of multiple co-crystallized inhibitors in the specific sEH binding site, obtaining a model directly placed in the pocket cavity of the enzyme, bearing the 3D information from multiple known co-crystallized inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, our research group has been involved in the discovery of novel soluble epoxide hydrolase inhibitors (sEHi) and, accordingly, the development of sEH 3D structure-based pharmacophore model represents a valuable strategy for accomplishing this aim [20,21]. Indeed, in addition to the identification of novel compounds with anti-inflammatory and anticancer activity targeting mPGES-1, representing another key target of our research interests [20,[22][23][24], we also focused on other targets belonging to the arachidonic acid cascade to identify multitarget agents with greater benefits than single-target inhibition [25]. In light of these premises, the 3D structure-based pharmacophore model was developed by collecting the necessary spatial definitions from the specific coordinates of multiple co-crystallized inhibitors in the specific sEH binding site, obtaining a model directly placed in the pocket cavity of the enzyme, bearing the 3D information from multiple known co-crystallized inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, only one inhibitor of mPGES1, CAY10526, was used. However, its efficacy and selectivity on mPGES1 has been confirmed (15)(16)(17) including in our previous report (7), and was even employed as reference compound (18). Experiments are currently undergoing including knock down of mPGES-1 by RNA silencing and exogenous PGE2 supplement for rescue.…”
Section: Abnormal Activation Of Specific Jak/stat Signal Results Inmentioning
confidence: 75%
“…Based on this preliminary finding, we chose CAY10526 (CAS:938069-71-7) to treat Hut78 cells. As several studies have shown that CAY10526 is an isoformselective inhibitor of PGE2 production through the selective modulation of mPGES-1 expression (15)(16)(17), and was even selected as reference compound when newer compound was synthesized and tested (18). The dose of CAY10526 used in the studies ranged from 1.8 to 300 ÎźM for different cells and experimental conditions, including our previous report showing CAY10526 [half inhibitory concentration (IC50): 16.7 ÎźM at 24 h] reduced PGE2 synthesis in primary T-cell acute lymphoblastic leukemia (T-ALL) cells (7).…”
Section: Mpges-1 Was Highly Expressed In Hut78 Cells and Suppression ...mentioning
confidence: 99%
“…Furthermore, the comparison of X‐ray structures of mPGES‐1 bound to GSH (PDB ID: 4AL0) [12] and its analogue (PDB code: 4AL1), [12] presenting a bulky biphenyl substituent, highlighted no significant conformational changes except a slight shift of Y130 residue. Also, the superposition of further mPGES‐1 structures co‐complexed with small molecules confirmed this outcome [13−15] …”
Section: Introductionmentioning
confidence: 61%